Stability analysis and control of an active suspension system [compact disc] - 241215 Kung, Kiew Li (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006